Iron (II) impregnated double-shelled hollow mesoporous silica as acid-base bifunctional catalyst for the conversion of low-quality oil to methyl esters. (May 2021) - Suryajaya, Stefanus Kevin; Mulyono, Yohanes Ricky; Santoso, Shella Permatasari; Yuliana, Maria; Kurniawan, Alfin; Ayucitra, Aning; Sun, Yueting; Hartono, Sandy Budi; Soetaredjo, Felycia Edi; Ismadji, Suryadi
Abstract: To promote the use of low-quality oils in producing biodiesel, a bifunctional acid-base catalyst Fe/DS-HMS-NH2 is fabricated using the two-step condensation technique. The obtained Fe/DS-HMS-NH2 is of a doubled shell structure in spherical shape with a uniform size of 156 nm. Its hollow core (with a diameter of 86 nm) and two spatial shells with different active sites enables the esterification and transesterification reactions to be accomplished in a one-pot synthesis. The influences of four independent reaction variables on the yield of fatty acid methyl esters Y F was studied, including catalyst loading m c, reaction time t, reaction temperature T, and the methanol to degummed palm oil mass ratio r m/o . The highest yield was obtained at 85.36% (w/w) when m c  = 6% (w/w), t  = 4.5 h, T  = 60 °C, and r m/o  = 6:1. The Fe/DS-HMS-NH2 shows a good recyclability with Y F > 80% (w/w) up to three reaction cycles. Graphical abstract: Image 1 Highlights: A novel acid-base bifunctional catalyst, Fe/DS-HMS-NH2, has been fabricated. Fe/DS-HMS-NH2 has been successfully employed to convert low-quality oil to FAME. 85.36% of FAME yield was achieved from low-quality oil using Fe/DS-HMS-NH2 . The fuel properties of the final FAME product conform to ASTM D6751 . Fe/DS-HMS-NH2 shows a good recyclability with FAME yield >80% up to the third run.